Chemical modification of titanium implant surfaces to accelerate osseointegration in implant treatment: Modifikasi permukaan titanium implan secara kimiawi untuk mempercepat oseointegrasi pada perawatan implan - Muh. Ramli Wardana; Irfan Dammar; Ade Lola Zafira (Makassar Dental Journal, 2026)
According to the 2018 Basic Health Research, the index of tooth loss in Indonesia is 19%. Dental implants are one of the treatments for tooth loss. The pre-valence of dental implant users has increased by 14% per year. The materials used for implants vary greatly, one of which is titanium. Titanium has high bio-compatibility, but its surface needs to be modified to accelerate osseointegration. Chemical surface modification changes the chemical properties of the car-rier surface to produce specific interactions between surface molecules and cells, which not only affects the surface properties of the cells but also causes changes in their internal structure and function. This literature review discusses various chemical methods that can be used to modify the surface of tita-nium implants to improve and accelerate the osseointegration process. It is concluded that modifications to the surface of dental titanium implants can alter the morphology and properties of the implant surface, thereby stimulating bone growth around the implant and improving the osseointegration process.